2008
DOI: 10.1111/j.1398-9995.2008.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucocorticoid receptor in nasal polyps by systemic and intranasal glucocorticoids

Abstract: GRalpha is downregulated in nasal polyps and upregulated by GC treatment. Neither GRalpha nor GRbeta appear to determine the sensitivity to GCs in nasal polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 36 publications
2
70
1
Order By: Relevance
“…In Pujols's study, the patients with nasal polyps were divided into GCtreated and untreated groups. 16 Even though there were steroid-insensitive individuals in the GC-treated group, because of the relatively small number, quantitative values of GRα and GRβ expression from such patients were likely masked by GRα and GRβ expression level in the majority of GC-sensitive patients. It may therefore be difficult to extrapolate from that data the actual quantitative levels of expression of the GRα and GRβ in the steroidinsensitive patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Pujols's study, the patients with nasal polyps were divided into GCtreated and untreated groups. 16 Even though there were steroid-insensitive individuals in the GC-treated group, because of the relatively small number, quantitative values of GRα and GRβ expression from such patients were likely masked by GRα and GRβ expression level in the majority of GC-sensitive patients. It may therefore be difficult to extrapolate from that data the actual quantitative levels of expression of the GRα and GRβ in the steroidinsensitive patients.…”
Section: Discussionmentioning
confidence: 95%
“…[14][15][16] These conflicting results may be explained by the different methodologies used. First, immunohistochemical studies do not accurately reflect the GR-α to GR-β ratio of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…They decrease polyp size, improve nasal airway patency, improve symptoms of rhinitis like rhinorrhoea, sneezing and nasal blockage, delay the recurrence of polyps after surgery and postpone the need for a new surgery [11]. The unusually wide range of GC actions can be explained by GC receptors present in three cell compartments: nucleus, cytoplasm, and plasma membrane.…”
Section: Medical Managementmentioning
confidence: 99%
“…This has led to the hypothesis that increased GR expression could impair the action of GC. Decreased expression of GR has also been recently reported in CRswNP with the use of a more reliable quantitative method of analysis [56,62,63]. More important than the expression of each individual isoform, GR -GR imbalance might be the most relevant determinant of GC resistance.…”
Section: Resistance To Gcmentioning
confidence: 99%
“…More important than the expression of each individual isoform, GR -GR imbalance might be the most relevant determinant of GC resistance. It is important to mention that some studies have demonstrated that CG therapy in CRSwNP does not change GR isoform expression or the GR -GR relation [56,63,64].…”
Section: Resistance To Gcmentioning
confidence: 99%